2000
DOI: 10.4049/jimmunol.164.1.436
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Activation of the Adenosine A2a Receptors Inhibits IL-12 Production by Human Monocytes

Abstract: Adenosine (ADO) exerts potent anti-inflammatory and immunosuppressive effects. In this paper we address the possibility that these effects are partly mediated by inhibition of the secretion of IL-12, a proinflammatory cytokine and a major inducer of Th1 responses. We demonstrate that 5′-N-ethylcarboxamidoadenosine (NECA), a nonspecific ADO analogue, and 2-p-(2-carbonyl-ethyl)phenylethylamino-5′-N-ethylcarboxamidoadenosine (CGS-21680), a specific A2a receptor agonist, dose-dependently inhibited, in whole blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
142
2
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(155 citation statements)
references
References 35 publications
7
142
2
4
Order By: Relevance
“…Stimulation of adenosine receptors has been shown to result in an anti-inflammatory, deactivated macrophage phenotype (16,17). In LPS-stimulated monocytes/macrophages, adenosine receptor activation attenuates the production of several proinflammatory cytokines, including TNF-␣ (18 -24) and IL-12 (22,25,26). In contrast to the suppressive effect of adenosine on the production of these proinflammatory mediators, adenosine up-regulates IL-10 production by LPS-stimulated monocytes/macrophages (22,26).…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Stimulation of adenosine receptors has been shown to result in an anti-inflammatory, deactivated macrophage phenotype (16,17). In LPS-stimulated monocytes/macrophages, adenosine receptor activation attenuates the production of several proinflammatory cytokines, including TNF-␣ (18 -24) and IL-12 (22,25,26). In contrast to the suppressive effect of adenosine on the production of these proinflammatory mediators, adenosine up-regulates IL-10 production by LPS-stimulated monocytes/macrophages (22,26).…”
mentioning
confidence: 76%
“…In LPS-stimulated monocytes/macrophages, adenosine receptor activation attenuates the production of several proinflammatory cytokines, including TNF-␣ (18 -24) and IL-12 (22,25,26). In contrast to the suppressive effect of adenosine on the production of these proinflammatory mediators, adenosine up-regulates IL-10 production by LPS-stimulated monocytes/macrophages (22,26). The mode of action of adenosine in up-regulating IL-10 production is unclear and so is the identity of receptors responsible for the adenosine enhancement of IL-10 production in LPS-activated macrophages.…”
mentioning
confidence: 99%
“…Activation of the A3AR, which inhibits adenylyl cyclase activity and decreases cAMP levels, may thus lead to the activation of NK cells. Link et al (2000) showed that a specific A2a receptor agonist inhibited the production of IL-12 in whole blood and monocyte cultures. In addition, in vivo studies by Hasko et al (1998) resulting in IL-12 downregulation, whereas low doses, as was used in this study, exclusively activate the A3AR and will results in IL-12 upregulation and potentiation of NK cell activity.…”
Section: A3 Adenosine Receptor Agonists Inhibit Colon Carcinoma G Ohamentioning
confidence: 99%
“…It has also been shown by other labs and us that LPS-induced IL-12 expression can be greatly downregulated by cAMP inducers [1], [13], [19], [20]. However there is little information about the mechanism for cAMP-signal-inhibitory effect on LPS-induced IL-12 expression in macrophages.…”
Section: Introductionmentioning
confidence: 99%